Kajian Escherichia coli Resisten Antibiotik pada Lingkungan Air di Indonesia - Yudith Elma Mauwalan; Novalino Kallau; Meity M Laut (Jurnal Veteriner Nusantara, 2022)
Water is a natural resource that is needed by living things. Esherichia coli is one of the normal flora on digestive tract of humans and animals and is a parameter of drinking water quality because its presence in the water indicates the water is contaminated. Esherichia coli is abundant in water and is a reservoir associated with Antimicrobial Resistance (AMR). This literature review aims to determine the prevalence level of Escherichia coli in the water environment in Indonesia and the level of Escherichia coli resistant to β-lactam antibiotics and aminoglycoside antibiotics. This literature review is obtained from searching and collecting data and information from various reference sources using the Mendeley and Google Schoolar applications. Research data on Escherichia coli resistance were analyzed and evaluated and it was found that the prevalence of Escherichia coli in the water environment in Indonesia ranges from 33.33% to 100% and the level of antibiotic resistance in the β-lactam group (Amoxicillin 66.7%-100%, Ampicillin 100% and Penicillin 100%) and Aminoglycosides (Streptomycin 73.3%-86.7%, Tobramycin 100%, Gentamicin 100% and Kanamycin 33.3%) against Escherichia coli in the water resources in Indonesia.